Clinical study on 16 cases of testicular torsion - Sato, N (Hinyokika kiyo. Acta urologica Japonica, 1989)
Sixteen cases of testicular torsion were experienced between 1983 and 1988. Diagnosis was confirmed by surgical exploration in all cases. The patients' age was between 10 and 31 years. Fourteen patients (88%) were in their second decade. The left side was involved in 13 cases, the right side in 2 and both sides in 1. Shortness of spermatic cord of involved side was observed in 12 cases (75%). This seemed to be one of the most important signs in differential diagnosis between testicular torsion and other acute scrotum. Prehn's sign was not available. Body temperature was more than 37 degrees C in only 1 case. Urinary tract infection was not noted. Orchiopexy was performed in 12 cases. 9 cases (75%) were treated within 24 hours after onset of the symptom. Two cases (13%) were operated more than 72 hours after onset, but repaired testis was not atrophic one year after surgery